The progress on how results based management has been implemented by appointed officials from 2013 to 2016: the case of Sanyati rural district council. - Mukute, Tendai Nomsa (Midlands State University, 2018)
The study sought to address the progress on how Results Based Management has been implemented by appointed officials from 2013 to 2016.The case of Sanyati RDC. The main objectives of this study are to evaluate the role of appointed officials in implementing Results Based Management against what they are doing , to know the impacts of the efforts and coming up with solutions to enhance their performance. Zimbabwean government in 2005 adopted RBM due to corruption, poor communication systems, poor technological advancement, poor budgeting, lack of monitoring and evaluation , focusing more on processes ,lack of accountability and transparency and poor performance had became the routine operation of the local authorities therefore resulting in poor service delivery. RBM emphasise on being result oriented instead of focusing on processes in order to achieve the intended objectives. Appointed officials as governance agents are responsible for service delivery and local economic development, the two become their objectives and it is their role to put in place strategies that are result oriented thus they play a significant role in RBM implementation. The researcher used empirical, theoretical and conceptual framework in this study to have an insight of what other scholars and countries have found on the research problem. Theories and models like the Results Based Management components , Open systems theory , Group dynamics theory ,New Public management theory to mention a few were used .Research methods like mixed method and descriptive research design, probability and non probability sampling techniques, primary and secondary data was collected through questionnaires, focus group discussions ,interviews with open ended and closed questions, journals articles and internet. Simple random and stratified sampling techniques were used as well. The targeted population of 112987people and the sample size was 90, 18 Councillors, 15 council employees including 6 Head of departments, 35 Sanyati residence, 12 Sector Ministries and 10 NGOs. Data gathered was presented and analysed using tabular, textual and graphical methods. The findings of the study revealed that appointed officials have a planning , budgeting ,monitoring and evaluation ,managerial and administrative role to play in the implementation of IRBM and in the process there are a number of challenges encountered which include lack of adequate training , skills ,resources , time, ,complexity of the document , congestion of policies , lack of consultation ,red tape , lack of motivation and unrealistic budgeting to mention just a few. Possible solutions like funding of the plans, further training of officials, and review of the document, stakeholder involvement, and introduction of local based strategies among others were suggested. RBM is also said to have benefited local authorities by improving service delivery and local economic development, a systematic way of meeting goals was developed, convenience of doing things and improved inclusion, transparency and accountability. The findings led to a realisation that, appointed officials plays a significant role for successful implementation and there is some progress in IRBM but there is need to capacitate the officials achieve the intended objective or results (outputs, outcomes and Outcomes).